2020
DOI: 10.31729/jnma.4693
|View full text |Cite
|
Sign up to set email alerts
|

Rare Cause of Tension Pneumothorax: Hydatid Disease of Lung: A Case Report

Abstract: Lung is the second most common site of hydatid disease, after liver. Pleural involvement of hydatiddisease can occur, and usually follows the rupture of a pulmonary or hepatic hydatid cyst into thepleural space. When a patient presents with tension pneumothorax, zoonotic infections, especiallyhydatid disease of the lung, also has to be considered especially in areas with high burden of thedisease. We report a 31 years male patient presenting with tension pneumothorax due to rupture ofhydatid cyst of lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Rupture in lung cysts may occur due to any condition leading to a rise in pulmonary or intra-abdominal pressure. 11 Tension pneumothorax is a rare complication of the pulmonary hydatid cyst and if acute it can manifest as severe tachycardia, tachypnea, jugular vein distention, and hypotension with unilateral diminished lung sounds, and trachea-mediastinal shift to the opposite side. 11 In our cases, symptoms such as intermittent dyspnea which had gradually worsened over time, accompanied by cough and expectoration of salty fluid, along with the hydatid disease being endemic in our region led us to suspect hydatidosis as the cause.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rupture in lung cysts may occur due to any condition leading to a rise in pulmonary or intra-abdominal pressure. 11 Tension pneumothorax is a rare complication of the pulmonary hydatid cyst and if acute it can manifest as severe tachycardia, tachypnea, jugular vein distention, and hypotension with unilateral diminished lung sounds, and trachea-mediastinal shift to the opposite side. 11 In our cases, symptoms such as intermittent dyspnea which had gradually worsened over time, accompanied by cough and expectoration of salty fluid, along with the hydatid disease being endemic in our region led us to suspect hydatidosis as the cause.…”
Section: Discussionmentioning
confidence: 99%
“…The initial treatment for tension pneumothorax accompanied by unstable hemodynamics is needle thoracostomy followed by chest tube insertion. When tension pneumothorax is caused by a ruptured pulmonary hydatid cyst, the main treatment is surgery with the aim of resecting the hydatid cysts without contamination of the pleural and mediastinal cavities 11 . Surgical techniques consist of enucleation (total removal of cyst), pericystectomy (removal of the first layer of the cyst), cystotomy with or without capitonnage of the pericystic space, and radical pulmonary resection 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common preoperative complications that may occur in pleural or lung hydatid disease include empyema and pneumothorax [30], but there are rare cases where, due to the rupture of the cysts, the patient can suffer from anaphylactic shock. There have even been cases of patients presenting with tension pneumothorax caused by the rupture of a lung cyst [31]. Several representative studies with patients with pulmonary hydatid cysts concluded that the rupture of the cyst in the pleural cavity is the most severe complication of the disease, alongside anaphylactic shock [32].…”
Section: Discussionmentioning
confidence: 99%